Price competition in ride-sharing platforms: a duopoly supply chain perspective - Kumar Jena, Sarat; Ghadge, Abhijeet (Elsevier, 2023)
A ride-sharing platform with a price-setting power mechanism exists in practice. However, it is unclear how supply chain transactions (ride price) and yields are affected due to a commission fee on ride-sharing platforms. To better understand, this study explores the impact of the service provider’s price-setting (Model S) and service enabler’s price-setting (Model E) power mechanism on supply chain profit under the influence of price competition in a sharing economy. We consider duopoly supply chains, wherein in one supply chain, a service provider delivers service through a service enabler, and in another, service providers offer direct customer service. Mathematical models are developed to analyze the difference in price-setting power mechanism effect, considering marketing efforts under different competitive scenarios. Results show that the supply chain profit is highest when the service provider sets the transaction price in Model S. Furthermore, when the commission fee exceeds a certain threshold (0.5), the total profit in Model E increases, but in Model S it decreases. In ride-sharing platforms, the service provider loses with a rise in commission fees, while the service enabler profits from it. The study contributes to the growing interest in the intricacies of sharing economy businesses.
Keywords: Sharing platform; Sharing economy; Ride-sharing; Competition; Duopoly supply chain; Marketing effort; Pricing